Overview of Agronomy Discipline in Agricultural Education of Bachelor of Science (Honours) in Agriculture - Shahane, Amit Anil; Shivay, Yashbir Singh (Chronicle of Bioresource Management, 2024)
The Dean Committee Report (DCR) is the most authentic recommendation for orientation of the agricultural education in India. As DCR is extensive, study of specific subject for its changes over the duration will be worthwhile. The present overview describes the agronomy subject for changes that occurred, relevance, background, and possible implications from 4th to 6th DCR (2007 to 2017; 2017 to 2024 and 2024 onwards). Maintaining same level of credit allocation (22, 21, 22, respectively during 4th, 5th, and 6th DCR), retaining the highest credits among all disciplines, increasing credits to elective courses (From 1, 4, and 16th respectively during 4th, 5th and 6th DCR), introduction of ‘Principles and practices of natural farming (2 credits) and increasing credits of organic farming combined with conservation agriculture to four signifies the importance of agronomy in Bachelor of Science (Honours) Agriculture (B.Sc. Agric.) disciplines. As overall courses and credits are increased consistently; it emphasizes over the 4th to 6th DCR on specification/specialization individually on soil management, plant management, and water management.